Pengaruh Financial Technology, Financial Knowledge, Financial Attitude, Financial Behavior, Dan Income Terhadap Financial Satisfaction Pada Pengguna Aplikasi BCA Mobile Di Kabupaten Lamongan - Imroatus Sakinah; Nadia Asandimitra Haryono; Harlina Meidiaswati (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study examines the influence of financial technology, financial knowledge, financial attitude, financial behavior, and income on financial satisfaction among BCA Mobile users in Lamongan Regency. The research is motivated by the rapid growth of digital financial services and the gap between financial inclusion and financial literacy. The objective is to analyze how these factors contribute to individuals’ financial satisfaction. This study uses a quantitative approach with primary data collected through online questionnaires from 160 respondents selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS 4. The results show that financial technology, financial knowledge, financial attitude, financial behavior, and income have positive and significant effects on financial satisfaction. The model demonstrates strong predictive power, indicating that these variables collectively explain a substantial portion of financial satisfaction. The findings highlight the importance of digital financial services, financial literacy, and responsible financial behavior in improving individual financial well-being.